2021
DOI: 10.1097/med.0000000000000693
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring in the hospital: an update in the era of COVID-19

Abstract: Purpose of review Continuous glucose monitoring (CGM) systems are Food and Drug Administration approved devices for the ambulatory setting; however, they remain investigational systems for inpatient use. This review summarizes the most recent and relevant literature on the use of continuous glucose monitoring in the hospital setting. Recent findings CGM provides real-time glucose data that enable healthcare professionals to make proactive and timelier clinical decisions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…[19][20][21][22][23] Previous studies have indicated that the factors impacting the use of CGM include CGMassociated costs, accessibility to healthcare providers, inadequate CGM training of healthcare workers, limited CGM-related knowledge of patients and inadequate support from CGM manufacturers. 24 A review demonstrated that the use of CGM in hospitalised patients has numerous advantages with minimal risks. [25][26][27] To promote the standardised use and management of CGM, China published the Chinese Clinical Guidelines for Continuous Glucose Monitoring in 2009, which were updated in 2012 and 2017.…”
Section: -14mentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23] Previous studies have indicated that the factors impacting the use of CGM include CGMassociated costs, accessibility to healthcare providers, inadequate CGM training of healthcare workers, limited CGM-related knowledge of patients and inadequate support from CGM manufacturers. 24 A review demonstrated that the use of CGM in hospitalised patients has numerous advantages with minimal risks. [25][26][27] To promote the standardised use and management of CGM, China published the Chinese Clinical Guidelines for Continuous Glucose Monitoring in 2009, which were updated in 2012 and 2017.…”
Section: -14mentioning
confidence: 99%
“…However, the use of CGM needs to be improved further 19–23. Previous studies have indicated that the factors impacting the use of CGM include CGM-associated costs, accessibility to healthcare providers, inadequate CGM training of healthcare workers, limited CGM-related knowledge of patients and inadequate support from CGM manufacturers 24. A review demonstrated that the use of CGM in hospitalised patients has numerous advantages with minimal risks 25–27.…”
Section: Introductionmentioning
confidence: 99%
“…CGM has not been formally approved for inpatient use at this time; however, during the COVID-19 pandemic, the Food and Drug Administration (FDA) issued guidance about the use of noninvasive remote monitoring devices, including CGM, in the inpatient setting and Dexcom recently received breakthrough designation for inpatient use to accelerate approval (https://www.fda.gov/regulatoryinformation/search-fda-guidance-documents/ enforcement-policy-noninvasive-remote-monitoring-devices-used-support-patient-monitoring-during). During the pandemic, studies exploring the feasibility and accuracy of CGM use in both critically and noncritically ill adults showed acceptable accuracy [44][45][46] and CGM data were safely used with a computerized algorithm to determine intravenous insulin infusion rates in critically ill patients [47].…”
Section: Inpatient Continuous Glucose Monitoring Usementioning
confidence: 99%
“…Several studies have shown that CGM devices can have many benefits when used in the hospital. 49 Among them is reducing hypoglycemia, 50 which is associated with adverse clinical outcomes. [51][52][53] In an early pilot study, RT-CGM devices and glucose telemetry were effective in providing remote glucose monitoring, with the potential to prevent inpatient hypoglycemia.…”
Section: Prevention Of Hypoglycemiamentioning
confidence: 99%